Role of the environment factors within inflammatory processes during polykistosis of ovaries - С. В. Гуньков; С. В. Бабич (Publishing House TRILIST, 2018)
Objective. To study the indicators of inflammatory process in women with polycystic ovary syndrome (PCOS) having equal body mass indices and in the absence of pathogenic infections, and to determine the content of trace elements. Material and methods. Two groups of women were selected. The first (control) group consisted of 57 healthy women of reproductive age. In the second (main) group were 64 women with PCOS. Using PCR method excluded the presence of pathogenic infections. The analysis of the frequency of inflammatory processes was based upon microscopic characteristics of vaginal microbiocenosis. For studying levels of manganese, nickel, zinc in serum, were selected 32 women from the control group and 44 women from the main group. Samples were analyzed on a mass spectrometer with an inductively coupled plasma. Validity of results was verified using Mann-Whitney U test, Student's t-test and χ2. Results. In the absence of sexually transmitted infections and equal body mass index, signs of inflammatory processes of vagina are much more common for women with PCOS. In control group, pathological samples were found in 10.52%, when as in group of women with PCOS - 84.38% (p = 0.000). For women with PCOS there was a tendency toward increase in the frequency of somatic diseases, but differences did not find statistical confirmation. The elevated levels of manganese and nickel exposure have been observed for women with PCOS. Authors associate elevated levels of zinc in the blood serum with the inflammatory process. Conclusion. In women with PCOS in absence of sexually transmitted infections and equal body mass index, signs of inflammation are much more common. Some role in vaginal microbiocenosis and inflammatory processes can play exposure to high levels of manganese and nickel.